Stall points : most companies stop growing--yours doesn't have to - Olson, Matthew S., 1951- (Yale University Press, 2008)
"Few large companies manage to avoid stalls in revenue growth with pronounced effects. The average company loses 74 percent of its market capitalization in the decade surrounding a growth stall, and the CEO and senior team turn over more than half the time. Stall Points answers the fundamental question at the heart of these downturns: Why do apparently healthy, successful companies suffer from an unexpected leveling or decline in revenues and profits and why is it so hard to recover?